Meningkatkan pembelajaran dalam pendidikan jasmani: Augmented reality berbasis aplikasi seluler untuk keterampilan motorik dasar - Pratama, Budiman Agung; Sucipto, Sucipto; Nanda Hanief, Yulingga (Universitas Nusantara PGRI Kediri, 2022)
The COVID-19 pandemic makes the physical education learning process take place distance learning so that students still have good fundamental motor skills. Interactive media can be used as an alternative to physical education learning. This study aimed to determine the use of interactive Augmented Reality Mobile App-Based media against Fundamental Motor skills 9-10 Years Old School Children. This research uses a quantitative approach, a type of quasi-experimental research, using matching-only. The samples in this study are 74 students of the basic sector aged 9-10 years, data collection for fundamental motor skills using TGMD-2, and data analysis using the t-test. The results showed that 2-tailed sig = 0.000 < 0.05, which explained that interactive media Augmented Reality Mobile App-Based affects fundamental Motor skills 9-10 Years Old School, Children. The study concludes that interactive media Augmented Reality Mobile App-Based can provide an increase in Fundamental Motor Skills in addition to the use of interactive media, Augmented Reality Mobile App-Based can be an alternative teaching media in physical education subjects.